TMEM16F Aggravates Neuronal Loss by Mediating Microglial Phagocytosis of Neurons in a Rat Experimental Cerebral Ischemia and Reperfusion Model - Zhang, Yijie; Li, Haiying; Li, Xiang; Wu, Jie; Xue, Tao; Wu, Jiang; Shen, Haitao; Li, Xiang; Shen, Meifen; Chen, Gang (Frontiers in Immunology, 2020)
Cerebral ischemia is a severe, acute condition, normally caused by cerebrovascular disease, and resulting in high rates of disability and death. Phagoptosis is a newly recognized form of cell death caused by phagocytosis of viable cells, and has been reported to contribute to neuronal loss in brain tissue after ischemic stroke. Previous data indicated that exposure of phosphatidylserine on viable neurons could induce microglial phagocytosis of such neurons. Phosphatidylserine can be reversibly exposed on viable cells as a result of a calcium-activated phospholipid scramblase named TMEM16F. TMEM16F-mediated phospholipid scrambling on platelet membranes is critical for hemostasis and thrombosis, which plays an important role in Scott syndrome and has been confirmed by many researches. However, few studies have investigated the association between TMEM16F and phagocytosis in ischemic stroke. In this study, a middle-cerebral-artery occlusion/reperfusion (MCAO/R) model was used in adult male Sprague-Dawley rats in vivo, and cultured neurons were exposed to oxygen-glucose deprivation/reoxygenation (OGD/R) to simulate cerebral ischemia-reperfusion (I/R) injury in vitro. We found that the protein level of TMEM16F was significantly increased at 12 h after I-R injury both in vivo and in vitro, and reversible phosphatidylserine exposure was confirmed in neurons undergoing I/R injury in vitro. Additionally, we constructed a LV-TMEM16F-RNAi transfection system to suppress the expression of TMEM16F during and after cerebral ischemia. As a result, TMEM16F knockdown alleviated the motor function injury and decreased the microglial phagocytosis of viable neurons in the penumbra through inhibiting the “eat-me” signal phosphatidylserine. Our data indicate that reducing neuronal phosphatidylserine-exposure via deficiency of TMEM16F blocks phagocytosis of neurons and rescues such stressed-but-still-viable neurons in the penumbra, which may contribute to reducing infarct volume and improving functional recovering.